Role of DGCR8 in mammalian pluripotency and innate immunity - Knol, Lisanne Iris (The University of Edinburgh, 2022)
DGCR8 is an RNA-binding protein involved in canonical micro (mi)RNA biogenesis as part of the nuclear microprocessor complex. While absence of DGCR8 in mammals is lethal, DGCR8 hemizygosity is observed in 22q11.2 deletion syndrome (22q11.2DS), the most frequently observed microdeletion in humans. 22q11.2DS is associated with aberrant immunity, neuropsychiatric disorders, and a range of developmental defects. To better understand the role of DGCR8 in immunity and development, CRISPR-Cas was used to create DGCR8 knockout and heterozygous PA-1 pluripotent cell lines. Different types of RNA sequencing revealed an altered transcriptomic landscape. As expected, DGCR8 knockout cells showed an overall decrease in mature miRNAs compared to wildtype levels, suggested to be caused by impaired primary miRNA processing. On the other hand, only a fraction of miRNAs in DGCR8 heterozygotes was differentially expressed. Notably, miRNAs in the miR-105/767 cluster were among the most downregulated among both knockout and heterozygote DGCR8 mutant cell lines. Pathway enrichment analysis for differently expressed transcripts suggested a defect in pluripotency in DGCR8 heterozygote cells, indicating that DGCR8 hemizygosity could have a more profound contribution to the developmental symptoms detected in 22q11.2 DS than previously anticipated. Lastly, we investigated the role of DGCR8 in antiviral immunity during pluripotency. While embryonic stem cells normally are unable to produce type-I interferons, Dgcr8-deficient mouse embryonic stem cells can mount an active interferon response when stimulated via the cytosolic RIG-I-like receptor pathway. This effect was contributed to the central role of mmu-miR-673 in suppressing the expression of Mitochondrial Antiviral Signalling Protein, leading to increased susceptibility to viral infections. These results highlight the importance of miRNAs in modulating mammalian innate immunity.
The role of DGCR8 in mammalian pluripotency and innate immunity
Keywords: MicroRNAs; RNA interference; MiRNA biogenesis; CRISPR-Cas9; Poly(I:C) transfections; PA-1 DGCR8; genome editing; Cas9-guideRNA mix; RT-qPCR